The role of the health sector in tackling climate change: A narrative review - Or, Zeynep; Seppänen, Anna-Veera (Health policy (Amsterdam), 2024)
•Healthcare sector contributes significantly to global warming, and its impact will increase with increasing demand for care.•There is growing evidence on effective green interventions which can be introduced by care providers.•These need to be generalised and supported by environmentally sustainable healthcare delivery strategies.•Efforts to reduce carbon footprint of healthcare can provide significant economic, organizational and health benefits. Climate change is one of the largest threats to population health and has already affected the ecosystem, food production, and health and wellbeing of populations all over the world. The healthcare sector is responsible for around 5 % of greenhouse gas emissions worldwide and can play a key role in reducing global warming. This narrative review summarized the information on the role of healthcare systems in addressing climate change and strategies for reducing its negative impact to illustrate different types of actions that can support the ecological transformation of healthcare systems to help reaching sustainable development goals. A wide range of green interventions are shown to be effective to reduce the carbon footprint of healthcare and can have a meaningful impact if implemented systematically. However, these would not suffice unless accompanied by systemic mitigation strategies altering how healthcare is provided and consumed. Sustainable healthcare strategies such as reducing waste and low-value care will have direct benefits for the environment while improving economic and health outcomes. The healthcare sector has a unique opportunity to leverage its position and resources to provide a comprehensive strategy for fighting climate change and improving population health and the environment on which it depends.